Indigenous Self-determination Under Settler Colonial Capitalism: Northern Territory Cattle Communities 1968–96. Issue 4 (2nd October 2019) - Rowse, Tim
Abstract : Using the papers of the Gibb Committee on the future of Aboriginal communities on pastoral properties in the Northern Territory (1970–72), this article contributes both theoretically and empirically to the history of self-determination policy. It reveals non-Aboriginal authorities' thinking at a crucial moment in the history of the governing of remote Aboriginal Australians: the dissolution of the 'pastoral-feudal' order under the impact of 'equal wages' and access to cash social security. The article argues that the state and pastoralists had to consider two modalities of Aboriginal empowerment: as individual citizen-workers whose labour time had now to be valued as a commodity; and as 'communities' aspiring to autonomy from the authority of pastoralists. The article concludes by arguing that the settler colonial state's imperatives are both 'capitalist' and 'custodial'.